HUBUNGAN STATUS GIZI DAN AKTIVITAS OLAHRAGA TERHADAP KEJADIAN DISMENOREA PRIMER PADA REMAJA PUTRI DI SMA WACHID HASYIM 2 TAMAN - Astrida Budiarti (Universitas Nahdlatul Ulama Surabaya, 2018)
Many girls experience primary dysmenorrhoea is affected by factors, including nutritional status and exercise activity. The purpose of this study was to analyze the relationship of nutritional status and sports activity to primary dysmenorrhoea in adolescent girls. This study used analytic observational design with cross sectional approach. The population is the students of class XI Intensive SMA MIPA Wachid Hasyim 2 Park that has experienced menstruation amounted to 59 people. The sampling technique is simple random sampling with 51 respondents. Instruments using questionnaires. Data were analyzed by Spearman Rank Correlation Test. The results showed that there was correlation between nutritional status and primary dysmenorrhoea occurrence, p = 0.001 (p <α = 0.05), and there was a correlation between exercise activity and primary dysmenorrhea, p = 0.001 (p <α = 0.05). This study show that the importance of education about a balanced diet with adequate nutritional intake to young women and to regular exercise because it affects the incidence of dysmenorrhoea.